Relationship between entrepreneurial competencies and entrepreneurial behavior among higher education students - Adeel, Shahzada (2024)
Entrepreneurship is an ability of individuals to turn ideas into actions, being acknowledged as an economic driver for society. It is also considered as an important factor for the market economy as it focusses on wealth and job creations. Entrepreneurship helps the society to eradicate poverty, enhance the innovation and increase its productive capacity. Considering, that the world is currently facing the consequences of the COVID19 pandemic, both economically and socially, it is even more relevant to promote entrepreneurship, as the creation of new companies is crucial to relaunch the economies of the countries affected by the pandemic. So, the promotion of entrepreneurship education becomes even more pressing. The governments and universities’ managers put their efforts to instil the entrepreneurial spirits on students, by promoting entrepreneurship courses in universities. However, some researchers found entrepreneurship education ineffective to develop the right skills among the university students, especially those related to the recognition of existing and overlooked opportunities. In order to better understand the most relevant competences that should be promoted in the context of entrepreneurship education, this study focused on the antecedents of entrepreneurial behaviour among higher education students, and how these are affected by gender and entrepreneurship education. More specifically, this study explores the concept of entrepreneurial alertness, how this concept has evolved since the seminal work Kirzner in 1973, through a literature review. In this case, the content analysis revealed five main research trends where entrepreneurial alertness is considered an element of the market process (2000-2004), a perceptual variable that influences an individual’s decision to become an entrepreneur (2005-2008), a dynamic capability of both entrepreneurs and employees (2009-2011), a skill that can be developed through education (2012-2017), and a factor that influences a firm’s performance and a source of competitive advantage (2018-2019). Therefore, over the years the research on entrepreneurial alertness has evolved from the focus on the individual to that of the company, and it is now recognized as a key factor of organizational success. Based on the literature review, it was proposed a theoretical model that explores the relationships among prior knowledge, entrepreneurial alertness, opportunity recognition, entrepreneurial motivation, entrepreneurial intention, and entrepreneurial behavior using a sample of 1290 students from three Portuguese universities. To test the hypotheses, data was analyzed using the SPSS-25 and AMOS-24 software. The results show that all relationships are positively significant, lending empirical support to the hypotheses. The empirical findings also indicate that entrepreneurial alertness and prior knowledge are the antecedents of opportunity recognition. Also, prior knowledge has a significant impact on entrepreneurial alertness and opportunity recognition. Moreover, prior knowledge has a stronger indirect impact on opportunity recognition through entrepreneurial alertness compared to its direct impact. Our results also revealed that entrepreneurial alertness has a stronger direct impact on opportunity recognition compared to its indirect impact through entrepreneurial motivation. In addition, entrepreneurial motivation positively influences the opportunity recognition and entrepreneurial intention. Likewise, opportunity recognition has a significant impact on entrepreneurial intentions which, in turn, positively influence the entrepreneurial behavior among higher education students in the Portuguese context. The results of the multi-group analysis showed that students enrolled in entrepreneurship education are better able to recognize opportunities by being alert, and to express higher entrepreneurial motivations and intentions, leading to superior entrepreneurial behaviour when compared to students without entrepreneurship education. Moreover, by comparing the responses of female and male students, the results indicate that female students show lower entrepreneurial alertness and opportunity recognition capacity when compared to their male counterparts. The present study is also novel in several ways. First, the present study has integrated previous constructs to form a comprehensive model. Second, the study explores the relationship between entrepreneurial alertness and development of specific personal motivations, which is not studied in literature. Third, there is no Portuguese study using this model that has been tested on higher education level students.